CsAP3: A Cucumber Homolog to Arabidopsis APETALA3 with Novel Characteristics - Sun, Jin-Jing; Li, Feng; Wang, Dong-Hui; Liu, Xiao-Feng; Li, Xia; Liu, Na; Gu, Hai-Tao; Zou, Cheng; Luo, Jing-Chu; He, Chao-Xing; Huang, San-Wen; Zhang, Xiao-Lan; et al. (Frontiers in Plant Science, 2016)
In our previous efforts to understand the regulatory mechanisms of cucumber unisexual flower development, we observed a stamen-specific down-regulation of the ethylene receptor CsETR1 in stage 6 female flowers of cucumber (Cucumis sativus L). This down-regulation is correlated with the primordial anther-specific DNA damage that characterizes inappropriate stamen development in cucumber female flowers. To understand how CsETR1 is down regulated in the stamen, we characterized a cucumber MADS box gene homologous to Arabidopsis AP3, CsAP3. We demonstrated that CsAP3 is functionally equivalent to the Arabidopsis B-class MADS gene AP3. However, three novel characteristics of CsAP3 were found. These include firstly, binding and activating CsETR1 promoter in vitro and in vivo; secondly, containing a GV repeat in its C-terminus, which is conserved in cucurbits and required for the transcription activation; and thirdly, decreased expression as the node number increases, which is similar to that found for CsETR1. These findings revealed not only the conserved function of CsAP3 as a B-class floral identity gene, but also its unique functions in regulation of female flower development in cucumber.